The The Influence of Pornographic Content on User Comfort on Twitter at Startup Qualitiva.id: Pengaruh Konten Pornografi Pada Kenyamanan Pengguna Twitter Di Startup Qualitiva.id - Ridho Amanatullah; Edi Surya Negara (Institute of Information Technology and Social Science (IITSS), 2022)
Social media, especially Twitter, has evolved into a focal point for the exchange of information and social interaction in the era of globalization and digital connectivity. While providing a platform for communication and knowledge sharing, the presence of pornographic content on Twitter poses significant challenges. This phenomenon gives rise to ethical dilemmas and fundamental questions regarding its impact on productivity, morality, and organizational culture. This study aims to investigate the influence of pornographic content on the comfort of Twitter users in Startup Qualitiva.id, utilizing the Webqual 4.0 method and Probability Sampling data collection technique, resulting in 43 respondents. Based on the conducted testing, it can be concluded that Twitter's filtration of pornographic content remains notably weak, and stricter policies are necessary to ensure user comfort, particularly in the work environment of Qualitiva.id, which, while relatively clean, is still contaminated by the frequent appearance of pornographic content on Twitter.